Evaluation of Imported Rice Distribution Governance During Production Surplus in the Context of Realizing Food Sovereignty in Garut Regency, West Java Province - Anwar, Zulaidi; Silaban, Himsar; Tumpal Pakpahan, Roy; Tumpal Pakpahan, Roy (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze in depth the effectiveness of the rice import policy, examine the shortcomings and obstacles in its implementation, and make relevant policy recommendations to achieve food sovereignty and positively impact farmer welfare. The results of the study indicate that the governance of imported rice distribution in Garut Regency still encounters obstacles ranging from infrastructure, misappropriation, and operational issues. However, relevant stakeholders in Garut Regency have made efforts by collaborating in monitoring and improvement. In addition, the import policy does not specifically impact the productivity of local farmers because the amount of rice production in Garut Regency is always a surplus, but if it is done continuously, imported rice can affect market stability. In addition, the phenomenon of imported rice is exploited by middlemen to suppress prices for farmers, resulting in a decrease in farmer motivation and a reduction in the number of farmers in Garut. Import policies can hinder food sovereignty because the government only focuses on fulfilling stocks rather than on the production process. Therefore, an evaluation of import policies is needed to achieve food sovereignty.